Socialization and Education on Biopore Infiltration Hole Construction at SMK Bina Profesi Pekanbaru Promoting Environmental Awareness and Sustainable Practices - Sari, Neri Puspita; Setiani, Yulia; Yasri, Desi; Zaiyar, Zaiyar; Rini, Silfia (Unram Journal of Community Service, 2024)
Pekanbaru has experienced frequent flooding due to high rainfall intensity, exacerbated by the reduction of water infiltration areas, which have been converted into residential and commercial zones. Additionally, poor environmental awareness is evident from waste accumulation along roadsides, obstructing drainage systems and contributing to surface runoff. With limited available land and reduced natural infiltration capacity, biopore infiltration holes offer a viable solution for mitigating waterlogging. Biopores facilitate rainwater absorption through artificial infiltration, effectively reducing surface runoff during heavy rains. This study focuses on the socialization and implementation of biopore infiltration holes at SMK Bina Profesi Pekanbaru. The process involved awareness programs for students, emphasizing the environmental benefits and construction techniques of biopores. Observations of the surrounding environment were conducted to assess water infiltration conditions, followed by the preparation and installation of biopores. The initiative not only aimed to reduce flood risks and runoff but also addressed waste management by utilizing organic waste in the biopore holes. Decomposed organic matter is converted into compost, promoting sustainable waste recycling. The biopore program at SMK Bina Profesi successfully educated students on both environmental stewardship and practical techniques for managing water infiltration, contributing to improved local sustainability efforts